2015
DOI: 10.2967/jnumed.115.159798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personal Characteristics and Technical Factors on Quantification of Sodium 18F-Fluoride Uptake in Human Arteries: Prospective Evaluation of Healthy Subjects

Abstract: Sodium 18 F-fluoride ( 18 F-NaF) PET/CT imaging is a promising imaging technique for the assessment of atherosclerosis but is hampered by a lack of validated quantification protocols. Both personal characteristics and technical factors can affect quantification of arterial 18 F-NaF uptake. This study investigated whether blood activity, renal function, injected dose, circulating time, and PET/CT system affect quantification of arterial 18 F-NaF uptake. Methods: Eighty-nine healthy subjects were prospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…The image analyst was masked to the subject’s demographics and to the image specifications. Arterial 18 F-FDG and Na 18 F uptake were quantified according to previously published methods [1315]. In summary, uptake of 18 F-FDG in the thoracic aorta was determined by manually placing an oval region of interest (ROI) around the outer perimeter of the artery on every slice of the axially oriented PET/CT images.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The image analyst was masked to the subject’s demographics and to the image specifications. Arterial 18 F-FDG and Na 18 F uptake were quantified according to previously published methods [1315]. In summary, uptake of 18 F-FDG in the thoracic aorta was determined by manually placing an oval region of interest (ROI) around the outer perimeter of the artery on every slice of the axially oriented PET/CT images.…”
Section: Methodsmentioning
confidence: 99%
“…First, FDG MAX and NaF MAX were adjusted for blood activity, injected dose and PET/CT technology by multivariable linear regression, because previous studies had indicated that these parameters significantly affect the quantification of arterial 18 F-FDG and Na 18 F uptake [15, 16]. Second, subject demographics are summarized by descriptive statistics and compared between healthy volunteers and patients using the unpaired Student’s t test, the Mann-Whitney U test, or Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of background FDG uptake (venous and muscle) was performed by placing regions of interest (ROI) and the average mean SUV was calculated. The background-corrected SUV was calculated as arterial SUV max minus the mean venous SUV (blood-subtracted SUV maximum: bsSUVmax) [19]. …”
Section: Methodsmentioning
confidence: 99%
“…38 For example, we have employed this methodology in detecting uptakes of FDG and NaF in atherosclerotic plaques with high sensitivity. 21,[44][45][46][47][48][49] Specifically, we have validated measurements of global coronary artery calcification with NaF-PET in animals and human studies.…”
mentioning
confidence: 99%